Risk factors associated with conduct disorder traits among high school participants in Turkey - Parna Prajapati; Mariam Rahmani; Ali Unlu; Andres Pumariega (Academia Mental Health & Well-Being)
Objective: To identify the risk factors associated with conduct disorder traits in a sample of Turkish high school participants. Methods: The survey encompassed 31,604 high school students, from which a final sample of 31,272 was selected for data analysis. The survey instrument had 66 questions in total with multiple sub-questions, and it was collected by the Istanbul Department of Education using trained counselors and teachers. The questions used to explore the risk factors associated with conduct disorder had sub-questions that were added to generate variables of interest used in this study. Linear regression between the dependent variable (conduct disorder traits) and independent variables (psychosocial and substance use) was used, with the level of significance set at p < 0.05. Results: The model explains about 13.2% and 11.6% of the variance in conduct disorder traits among male and female participants, respectively. Participants with high anomie, high irritability, high religious self-practices, and less religious beliefs were significantly more likely to have higher conduct disorder traits scores. The participant characteristics that had significantly low conduct disorder traits scores include those who spent less time with peers, spent more time with family, had more parental involvement, low family substance use, high peer influence, better school grades, higher depression and anxiety scores, and those with low substance use. Conclusion: In this data, many statistically significant risk factors were associated with the development of conduct disorder traits. This is the first study to report risk factors for conduct disorder traits in a large sample of Turkish youth.